Acculturation and psychological well-being among Middle Eastern migrants in Australia: The mediating role of social support and perceived discrimination. (September 2019) - Hashemi, Neda; Marzban, Maryam; Sebar, Bernadette; Harris, Neil
Abstract: Objectives: The aim of this study is to examine the relative contribution of acculturation, perceived social support, and perceived discrimination on psychological well-being (PWB) among Middle Eastern (ME) migrants in Australia. Method(s): A cross-sectional study was conducted in Queensland, Australia. A total of 382 first-generation young adult (aged 20–39 years) ME migrants completed a self-administered questionnaire. The hypothesised model was tested through a two-step process: measurement, and structural model testing. First, Confirmatory Factor Analysis (CFA) was applied to test the fit of the measurement model and reliability and validity indices were calculated. Structural Equations Modelling (SEM) was then used to test the structural model. The significance of the mediating effect was tested using bootstrapping method. Results: Mainstream acculturation had the greatest accumulated total effect on PWB through both a direct and an indirect effect via perceived discrimination. Ethnic acculturation had the second greatest total effect on PWB, with both a direct effect and indirect effects through perceived social support and perceived discrimination. Perceived discrimination demonstrated both a direct effect and an indirect effect on PWB through perceived social support. Perceived social support had only a direct effect on PWB. Conclusions: Facilitating ME migrants' active participation in both ethnic and mainstream societies is important. Moreover, developing ethnic communities associations and resources could be an effective option to provide social support to ME migrants and in turn to improve their PWB. To provide ME migrants with better mental health outcomes, there is still a need to minimize the discrimination against them.